The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11061139
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Cowpea Challenges in West Africa for Food Security: Analysis of Factors Driving Yield Gap in Benin

Abstract: Feeding the world in 2050 requires us to find ways to boost yields of the main local crops. Among those crops, cowpea is one of the grain legumes that is playing an important role in the livelihood of millions of people in West Africa, especially in Benin. Unfortunately, cowpea on-farm yields are very low. In order to understand the main factors explaining cowpea yield gaps, we collected and analyzed detailed survey data from 298 cowpea fields in Benin during the 2017, 2018 and 2019′s rainy seasons, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In the study of Munjonji, Ayisi [11], a biomass yield of more than 2 t/ha was reported for cowpea under water stress conditions. The 2017 grain yield levels were lower but were in the range of what is obtainable and reported under rainfed conditions in many smallholder farming sectors [9]. Despite the low yields, mulching showed that it has a potential to increase the biomass and grain yield of cowpea.…”
Section: Agronomic Parametersmentioning
confidence: 75%
See 1 more Smart Citation
“…In the study of Munjonji, Ayisi [11], a biomass yield of more than 2 t/ha was reported for cowpea under water stress conditions. The 2017 grain yield levels were lower but were in the range of what is obtainable and reported under rainfed conditions in many smallholder farming sectors [9]. Despite the low yields, mulching showed that it has a potential to increase the biomass and grain yield of cowpea.…”
Section: Agronomic Parametersmentioning
confidence: 75%
“…Cowpea (Vigna unguiculata (L.) Walp) is an important protein-rich food consumed by rural and urban communities of Africa and other countries [8]. Most of the cowpea is produced by smallholder farmers who are resource poor and farm on marginal soils [9]. Thus, it is critical for these farmers who cannot afford inorganic fertilisers or manures to maximise on biologically fixed nitrogen and the retention of high-quality organic residues in their soils.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, barriers to scaling legume seed systems focused on the challenges and obstacles that limit the expansion of seed systems such as policy constraints or inadequate infrastructure. Barrier Legume crop References Poor soil quality affects the performance of some varieties thereby reducing the likelihood of adoption by smallholders Cowpea Anago et al ( 2021 ) Some legume crops/varieties have a greater susceptibility to pests and diseases resulting in lower yields. This can act as a barrier to the adoption of some legume varieties/crops by smallholders.…”
Section: Resultsmentioning
confidence: 99%
“…This can act as a barrier to the adoption of some legume varieties/crops by smallholders. Cowpea Anago et al ( 2021 ) Aflatoxin contamination negatively influences the cultivation of groundnuts in some smallholder farming communities Groundnut Boni et al ( 2021 ) Antinutrients in legume products can deter smallholders from producing/consuming certain legumes Grass pea Girma et al ( 2011 ) Restrictive policies can make the trade of legume seeds difficult Multiple Mulesa and Westengen ( 2020 ) COVID-19 had a severe negative impact on seed trade in the region Common bean Nchanji and Lutomia ( 2021 ) Lack of improved varieties (incl. early generation seed) and high seed cost Groundnut Sinare et al ( 2021 ) Limited access to land and gender issues around land tenure security (socio-economic factors) Multiple, groundnut Branca et al ( 2021 ); Sinare et al ( 2021 ) Limited access to other agronomic inputs (such as tools and fertilizers) Multiple Branca et al ( 2021 ) Insufficient access to credit and extension services Multiple Branca et al ( 2021 ) …”
Section: Resultsmentioning
confidence: 99%
“…Agricultural productivity is increasingly low due to progressive soil degradation and nutrient depletion 1 , 2 . Main soil nutrients (N, P, and K) as well as secondary and micro-nutrients are removed through harvesting, leaching, denitrification, erosion, and run-off.…”
Section: Introductionmentioning
confidence: 99%